Some Studies on Cutting Force Generation in Machining of Mg-Ca1.0 Alloy - Jagtap, Ketan; Sanap, Suresh (Journal of Graphic Era University, 2024)
Magnesium alloy has qualities that are similar to those of bone, it is now commonly acknowledged as a biodegradable material. Mg-Ca1.0 is a recently developed biodegradable substance that doesn’t cause any harmful substances to be produced in the body. It is frequently utilized in fixation screws and supporting plates for bone implants. To far, very little research has been published on the machining of biodegradable Magnesium Calcium alloy. This investigation’s goal is to evaluate the cutting forces produced during a face milling procedure. The experimental work used a one-factor-at-a-time strategy to assess how process factors affect performance attributes. The current study uses a CVD diamond-coated insert to examine how the depth of cut, feed rate, and cutting speed affect the radial (Fx), tangential (Fy), and axial (Fz) cutting forces during face milling in a dry machining environment.